Dentin hypersensitivity treatment with ozonated oil: a randomized controlled triple-blind clinical trial (Research, Society and Development, 2021)
The present study aimed to assess dentin hypersensitivity (DH) level and quality of life in patients before and after treatment with ozonated oil compared with extra virgin oil. This is a randomized triple-blind controlled clinical trial, consisting of patients with dentin hypersensitivity which was stimulated by evaporative and thermal stimuli. DH level was measured using a numerical rating scale. The patients were treated with ozonated oil and olive oil. Data were measured at baseline, immediately, and 4 weeks after treatment. The Dentine Hypersensitivity Experience Questionnaire (DHEQ-15) and the Oral Health Impact Profile (OHIP-14) were applied at baseline and 4 weeks after treatment. The sample consisted of 8 women and 3 men, with an average age of 23.82 years. The test group was 40 teeth while the control group consisted of 36 teeth, with the most prevalent tooth being the incisor (52.6%). There was a significant reduction in the DH level and an improvement in the quality of life after treatment. Among the sample, 90.1% reported an improvement in the final result. Both ozonated oil and olive oil were effective in reducing dentin hypersensitivity level and improving oral health-related quality of life 30 days after treatment.